Attitudes of Secondary Level Teachers towards EMI in English Medium Schools of Mahendranagar - Ojha, Jay Raj (Journal of Bhuwanishankar, 2022)
English Medium Instruction (EMI) is a growing phenomenon in Nepalese private school education. Learning engagement through EMI in different subjects is believed to be effective for developing learners’ communicative competence and comprehension skills. However, The English proficiency of the teachers, and their positive attitude towards English language and the use of judicious classroom language policy are considered crucial for the effective output of EMI without affecting the learners’ mother tongue. In this context, this study aimed to present the attitudes of secondary-level teachers towards English Medium of Instructions (EMI). It further attempted to find out the effects and challenges of EMI in the context of English medium schools in Mahendranagar, Kanchanpur. A qualitative phenomenological design was employed to extract the lived experiences of the participants with EMI. The researcher adopted a non-random convenience sampling method to collect information from two secondary-level teachers teaching Mathematics and Science at private English-medium schools in Mahendranagar, Kanchanpur. Semi-structured interviews were conducted to collect the lived experiences of the participants with EMI. The findings of this study revealed that teachers were positive towards EMI although they encountered challenges to its effective implementation. The results imply that EMI helps teachers in their profession, as competent English-Medium instructors are well paid and offered better career opportunities. Similarly, it creates a platform for the learners to develop communicative competence in English and meet their career goals. Despite these plus sides, EMI can pose a threat to our national or local languages if it is used exclusively without appropriate and judicious language policy.